Multipole and multimode engineering in Mie resonance-based metastructures - Liu, Tianji; Xu, Rongyang; Yu, Peng; Wang, Zhiming; Takahara, Junichi (Nanophotonics (Berlin, Germany), 2020)
Benefited from the well-known Mie resonance, a plethora of physical phenomena and applications are attracting attention in current research on dielectric-based nanophotonics. High-index dielectric metastructures are favorable to enhance light-matter interaction in nanoscale with advantages such as low loss, optical magnetism, and multipolar responses, which are superior to their plasmonic counterpart. In this review, we highlight the important role played by Mie resonance-based multipolar and multimodal interaction in nanophotonics, introducing the concept of “multipole and multimode engineering” in artificially engineered dielectric-based metastructures and providing an overview of the recent progress of this fast-developing area. The scope of multipole and multimode engineering is restricted not only in multipolar interferences of meta-atom and meta-molecule but also in the nontrivial intermodal coupling (Fano resonance and bound states in the continuum), in the collective mode and the surface lattice mode appearing via periodic meta-lattices and aperiodic meta-assembly, in chiral enhancement via chiral and achiral dielectric metastructures, and in Mie resonance-mediated hybrid structures (Mie-plasmon and Mie-exciton). Detailed examples and the underlying physics of this area are discussed in-depth, in order to lead the multifunctional metastructures for novel applications in the future.